Pressure Dependence of Crystal Structure and Ionic Conductivity on Composite Glass (AgI)0.7(AgPO3)0.3 - S. Suminta; E. Kartini; Mardiyanto Mardiyanto; W.A. Adi (PPIKSN-BATAN, 2005)
The superionic composite glass, (AgI)0.7(AgPO3)0.3 has been succesfully synthesized by melt quenching method. The crystall structure of coin type composite glass at various pressure of 100, 300 and 700 kg/cm2 have been measured by using an X-ray Difractometer at PTBIN-BATAN. The X-ray difraction pattern shows some Bragg peaks correspond to the crystaline γ-AgI. The increasing of pressure result the peaks become broaden and shift to the lower angle. This indicates that the crystal size is decreasing and the microstrain is increasing. Three strong peaks at (111), (220) and (311) have been analyzed by using a Gaussian Fitting. Based on calculation, crystal size (D) of (AgI)0.7(AgPO3)0.3 at pressures of 100, 300 and 700 kg/cm2 are 1114 Å, 13165 Å and 7240 Å respectively, while microstrain values (η) are 4 x 10-3 (1), 7.5 x 10-3 (4) and 8 x 10-3 (4). The composite glass (AgI)0.7(AgPO3)0.3 crystal structures at pressures of 100, 300 and 700 kg/cm2 have been analyzed by using a Rietveld method. The refinement results show that the peaks correspond to γ-AgI phase with a symmetry space group F-4 3 m No. 216, FCC, with the lattice constant namely 6.518(3), 6.508(3) and 6.506Ǻ(2) at a pressure of 100, 300 and 700 kg/cm2 respectively. The increasing of microstrain (η), and crystal size (D) and the decreasing of lattice constant (a) will increase the ionic mobility, thus increasing the ionic conductivity. The function of pressure on melt γ-AgI phase into glass matrix AgPO3 decreases the lattice constant and the crystal size, cause the increasing of microstrain broadening and ionic conductivity